The socio-economic impacts of Covid-19 restrictions: Data from the coastal city of Mombasa, Kenya - Kithiia, Justus (Data Brief, 2020)
The novel corona virus disease (Covid-19) outbreak has caused great uncertainty in all spheres of human life. The experience has been incredibly humbling given that no country or section of society, regardless of its wealth or status, has been spared. The pandemic is not only a health crisis, but is also having serious damaging effects on societies, economies and vulnerable groups. Timely response is necessary in order to alleviate human suffering and to prevent irreversible destruction of livelihoods. This paper provides preliminary data on the socio-economic impacts of Covid-19 in the coastal city of Mombasa, Kenya, at the time of government-imposed curfews and cessation of movement. We conducted online surveys for two weeks during the restrictions period. The data was collected using online questionnaires directed at the city residents. The data highlights the mobile gender gap resulting from gender inequalities, residents’ reliance on the government for Covid-19 information but lack of trust for government interventions, inadequate provisions of essential services, and the residents’ lack of preparedness to tackle similar challenges in the future.